Aquatic foods at the nutrition–environment nexus - Koehn, Zachary; Leape, Jim; Allison, Edward (Eddie) (Nature Research, 2023)
A recent analysis of the environmental footprint of the world’s food systems found that aquatic foods, which include all fish, shellfish and seaweeds that are farmed or harvested in marine or freshwater environments, supply only 1% of food produced globally but are responsible for 10% of cumulative environmental impacts of food production. This statistic obscures two vital facts about the role of aquatic foods in food systems: first, that while aquatic foods account for a small proportion of total food production, they are an important source of vital nutrients; and second, that while some aquatic foods place substantial pressure on environmental systems, there are hundreds of aquatic foods that offer highly sustainable options.